Carotid intima–media thickness, but not chronic kidney disease independently associates with noncardiac arterial vascular events in South Africa. Issue 4 (April 2019) - Kolkenbeck-Ruh, Andrea; Woodiwiss, Angela J.; Naran, Ravi; Sadiq, Eitzaz; Robinson, Chanel; Motau, Tshegofatso H.; Monareng, Taalib; Mabena, Philanathi; Manyatsi, Nomvuyo; Gazwa, Pitchou Z.; Abdool-Carrim, Talib; Majane, Olebogeng H.I.; et al.
Abstract : Aim: Although chronic kidney disease (CKD) as determined from estimated glomerular filtration rate (eGFR) is recommended for risk prediction by current hypertension guidelines, the equations to derive eGFR may not perform well in black Africans. We compared whether across the adult lifespan, eGFR or CKD are as closely associated with noncardiac arterial vascular events, as carotid intima–media thickness (IMT), in Africa. Methods: In 1152 black South Africans [480 with noncardiac arterial events (294 with critical lower limb ischemia, 186 with stroke) of which 37% were premature] and 672 age, sex and ethnicity-matched controls from a randomly selected community sample, we assessed relations between eGFR, CKD or carotid IMT (B-mode ultrasound) and arterial events. Results: From 20 years until old age, with or without adjustments, IMT was increased in those with as compared with without events ( P < 0.01 at each decade of age). However, at any decade of age across the adult lifespan neither creatinine concentrations, nor eGFR were altered in those with arterial events ( P > 0.28). Although IMT was strongly and independently associated with the odds of an event [odds ratio per 1 SD (0.171 mm) effect = 2.19, confidence interval = 1.75–2.78, P < 0.0001], neither creatinine concentrations ( P = 0.89), modification of diet in renal disease-derived ( P = 0.07), nor Chronic Kidney Disease Epidemiology Collaboration-derived [odds ratio per 1 SD (22.5 ml/min per 1.73 m 2 ) effect = 1.06, confidence interval = 0.89–1.27, P = 0.51] eGFR were independently associated with the odds of an event. Although many with premature events had an increased IMT (63%), few with either premature events (8%) or with events at an older age (21%) had CKD and CKD had a poor performance (0.539 ± 0.011) and low sensitivity (16%) for event detection. Conclusion: In black South Africans, despite carotid IMT strongly associating with noncardiac arterial vascular events (stroke and critical lower limb ischaemia) consistently across the adult lifespan, few with events have CKD and CKD fails to associate with events. Abstract : Supplemental Digital Content is available in the text